Draft genome sequence of Staphylococcus aureus strain HD1410, isolated from a persistent nasal carrier - Nurjadi, Dennis; Boutin, Sébastien; Dalpke, Alexander; Heeg, Klaus; Zanger, Philipp (Genome announcements, 2018)
We report here the draft genome sequence of a Staphylococcus aureus strain isolated from the nares of an 18-year-old female healthy persistent-carrier individual, and it was used to investigate S. aureus-specific immune responses in colonized and noncolonized individuals.